2018
DOI: 10.1292/jvms.17-0665
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime behavioral study of flying foxes on the southern coast of West Java, Indonesia

Abstract: Flying foxes are important in the maintenance of forests and diversity. However, knowledge of their behavioral ecology, especially of movement and foraging patterns, which are essential for conservation and management of their populations, are not well known. Therefore, movement behavior of two individuals of Pteropus vampyrus were examined using an Argos telemetry system, and foraging pattern of Pteropus spp. was directly observed, at West Java province, Indonesia in October 2017. The maximum distance between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…While many species within the Pteropodidae family rely on ephemeral roosts and frequent changes of roost sites (Storz et al ., 2000; Rollinson et al ., 2014; Hengjan et al ., 2018), other species consistently return to traditional roosts over many days, or even years. In our study, Egyptian fruit bats roosted in abandoned mud‐brick houses in a semi‐permanent manner, most likely resulting from the high likelihood of human disturbance.…”
Section: Discussionmentioning
confidence: 98%
“…While many species within the Pteropodidae family rely on ephemeral roosts and frequent changes of roost sites (Storz et al ., 2000; Rollinson et al ., 2014; Hengjan et al ., 2018), other species consistently return to traditional roosts over many days, or even years. In our study, Egyptian fruit bats roosted in abandoned mud‐brick houses in a semi‐permanent manner, most likely resulting from the high likelihood of human disturbance.…”
Section: Discussionmentioning
confidence: 98%
“…C. titthaecheilus and R. leschenaultii were medium size pteropodids and the observations done of this two genus showed that they did not undergo daily torpor (Barclay et al, ; McNab & Bonaccorso, ). Meanwhile, P. vampyrus is a large size pteropodid which is always at positive energy state; therefore, it does not require torpor (McNab & Bonaccorso, ); and instead, they fulfil their energy by foraging food all the time (Hengjan et al, ). However, with the capacity of the red pulp vascular space to store blood, all three species of bats might undergo torpor during extreme conditions or in condition when the food is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The decline of tree and fruit populations in forests, forest fires and extreme climate change often lead to the foray of fruit bats into human farming areas, especially during the fruiting season (Basri et al, ; Páez, Restif, Eby, & Plowright, ). Large‐sized fruit bats, such as flying foxes, are nomadic foragers capable of flying up to 100 km from the roosting site in one night (Hengjan et al, ). Fruit bats, being social beings, are reported to engage in conflicts over food with other species such as monkeys (Hengjan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Acquisition rates for spatial data were heterogeneous among individuals [ 42 ]. Because [ 49 ] found that Pteropus spp . spent an average 12.0 min (range: 1–67 min) and 25.0 min (range: 10–40 min) searching for and consuming fruits in fig and mango trees respectively, only GPS devices recording one location every 5 min were considered.…”
Section: Methodsmentioning
confidence: 99%